Economic burden of malignant blood disorders across Europe: A population-based cost analysis - Burns, R; Leal, J; Sullivan, R; Luengo-Fernandez, R (Elsevier, 2016)
Background: Malignant blood disorders are a leading contributor to cancer incidence and mortality across Europe. Despite their burden, no study has assessed the economic effect of blood cancers in Europe. We aimed to assess the economic burden of malignant blood disorders across the 28 countries in the European Union (EU), Iceland, Norway, and Switzerland. Methods: Malignant blood disorder-related costs were estimated for 28 EU countries, Iceland, Norway, and Switzerland for 2012. Country-specific costs were estimated with aggregate data on morbidity, mortality, and health-care resource use obtained from international and national sources. Health-care costs were estimated from expenditure on primary, outpatient, emergency, inpatient care, and drugs. Costs of informal care and productivity losses due to morbidity and early death were also included. For countries in the EU, malignant blood disorders were compared with the economic burden of overall cancer. Findings: Malignant blood disorders cost the 31 European countries €12 billion in 2012. Health-care cost €7·3 billion (62% of total costs), productivity losses cost €3·6 billion (30%), and informal care cost €1 billion (8%). For the EU countries, malignant blood disorders cost €6·8 billion (12%) of the total health-care expenditure on cancer (€57 billion), with this proportion being second only to breast cancer. In terms of total cancer costs in the EU (€143 billion), malignant blood disorders cost €12 billion (8%). Interpretation: Malignant blood disorders represent a leading cause of death, health-care service use, and costs, not only to European health-care systems, but to society overall. Our results add to essential public health knowledge needed for effective national cancer-control planning and priorities for public research funding. Funding: European Hematology Association.